Patient education in the hospital-at-home care context - Heli Vaartio-Rajalin; Linda Nyholm; Lisbeth Fagerström (The Beryl Institute, 2020)
The objective of this study is to describe adult patients' and their family caregivers' experiences of patient education in the hospital-at-home care context. Methods included a cross-sectional descriptive study including three hospital-at-home units in Finland. Adult, non-palliative patients (n = 27) and their family caregivers (n = 18) were interviewed pairwise by telephone, and the data analyzed with inductive thematic content analysis. COREQ guidelines were used to plan and guide the study design. Results concluded both patients and family caregivers seemed to have quite similar knowledge expectations, which only differs slightly from findings in other in- or outpatient contexts. In the hospital-at-home context, there is an evident need for clinical coaching and guidance in relation to self-care activities and for future-oriented education about the services available after hospital-at-home care. Six themes describing patients' and family caregivers' experiences of patient education in the hospital-at-home care context emerged, from patient-centered, goal-oriented and empowering education to the bypassed education of both patients and family caregivers. We conclude that in the hospital-at-home care context, the patient is not alone in his/her illness but instead the patient and family caregiver together form a unit. Thus, the need exists for extended, iterative patient education in hospital-at-home care: need for clinical coaching, guidance and support in relation to self-care activities and for future-oriented education about the services available after HAH care. Such extended patient education, in which patients' family caregivers were included, strengthens the patient-family caregiver relationship, minimizes caregiver burden and the need for additional healthcare services. Experience Framework This article is associated with the Patient, Family & Community Engagement lens of The Beryl Institute Experience Framework. (http://bit.ly/ExperienceFramework) <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Patient%2C%20Family%20%26%20Community%20Engagement%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.